ANALISA SISTEM INFORMASI AKUNTANSI GAJI DAN UPAH DALAM RANGKA PENGENDALIAN INTEREN PADA PT. XYZ - Alcianno G. Gani (JURNAL MITRA MANAJEMEN, 2020)
ABSTRACTThe wage and salary accounting system is a framework of procedures that are interconnected according to a comprehensive scheme for carrying out the main activities and functions of the company, Internal control is an element of the system that includes the organizational structure, methods and measures which are combined to maintain organizational wealth, check reliability and the rigor of accounting data, encourages competence and encourages compliance with management regulations PT XYZ's salary and wage accounting information system is not in accordance with the supporting theory, although it can be assisted with fingerprint software, Ms Office Excel, and the Accurate Accouting System, but related functions are still not ideal, so that internal control in the salary accounting information system and wages can still be increased, namely in the related functions section, where the division and division of duties are dominant in the financial sector, by forming parts that do not exist such as the employment function, PPh21 function, and other functions, in accordance with the prevailing theory. In the context of internal control of the salary and wage accounting information system, companies are advised to add a performance management system in the form of KPI (key performance indicator). Keywords: The wage and salary accounting system, internal control, performance management System